Ngaku (?), Mário Pinto de Andrade (Ukamba), Mwama Huta e Mwe Muliata Ngongola (sentado). Frente Leste, Angola
Ngaku (?), Mário Pinto de Andrade (Ukamba), Mwama Huta e Mwe Muliata Ngongola (sentado). Frente Leste. Angola.